Characteristics and outcome of fetal nuchal translucency above 3.5 mm in the fi rst trimester - Cátia Lourenço; Inês Gouveia; Ana Carriço; Francisco Valente (Open Journal of Biological Sciences - Peertechz Publications, 2019)
Objective: To describe the natural history of fetuses with a nuchal translucency (NT) above 3.5 mm when crown-rump length measures between 45 and 84 mm. Methods: We performed a retrospective cohort study of fetuses with fi rst trimester NT above 3.5 mm between January 2013 and March 2017. Results: A total of 75 cases with NT above 3.5 mm in the fi rst trimester were identifi ed. 3 cases were excluded (lost to follow-up), so that 72 cases were included. There were additional fi rst trimester markers of aneuploidy in 16 cases and 5 cases of major structural abnormalities diagnosed in the fi rst trimester ultrasound. 2 cases declined invasive testing. The karyotype was abnormal in 30 cases (43%), including 17 cases of trisomy 21. There were 25 terminations of pregnancy (34.7%), 11 fetal deaths (15.3%) and 36 livebirths (50%). The 36 live-born infants were followed. In this group 3 cases of trisomy 21, 1 case of unilateral hypoplasia of orbicularis oris, 1 Noonan-like syndrome, 1 case of 8p23.1 duplication (benign variant) and 1 case of lower limb lymphedema were observed.